2012
DOI: 10.1177/0961203312436861
|View full text |Cite
|
Sign up to set email alerts
|

Statin-induced lupus: a case/non-case study in a nationwide pharmacovigilance database

Abstract: Statin use has been advocated to prevent atheromatous complications in lupus patients and may be widely prescribed for these patients in future. Statin-induced lupus has also been described, though the risk is not confirmed. The goal of this study was to detect a safety signal regarding statin-induced lupus. We conducted a case/non-case study in the French PharmacoVigilance Database from January 2000 until December 2010. Cases were drug-induced lupus reports. Non-cases were all reports of other adverse drug re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 13 publications
3
13
0
4
Order By: Relevance
“…The toxicities reported to the French PV database were similar to those observed during the development of bevacizumab [22]. A review of the same database for drugs associated with induced immune thrombocytopenic purpura also found Bevacizumab in association with thrombocytopenia [23].…”
Section: Postmarketing Publicationssupporting
confidence: 55%
“…The toxicities reported to the French PV database were similar to those observed during the development of bevacizumab [22]. A review of the same database for drugs associated with induced immune thrombocytopenic purpura also found Bevacizumab in association with thrombocytopenia [23].…”
Section: Postmarketing Publicationssupporting
confidence: 55%
“…Exposure to statins was present in 17 (7.3%) cases and in 10,601 (4.7%) non-cases. Reporting odds ratio (ROR) for statin exposure associated with lupus erythematosus was 1.67 (ROR was > 1 for each statin but fluvastatin) [71]. Taking into account the small number of cases with statin therapy (n = 17) these results should be further confirmed in other studies.…”
Section: Rheumatic Diseases and Statin Intolerancementioning
confidence: 89%
“…Several case/non-case studies showed that statins might have been significantly associated with an increased risk of polymyalgia rheumatica (n = 327 cases; reporting odds ratio (ROR) 14.21) [69], rheumatoid arthritis (n = 508 patients; adjusted OR = 1.71, p = 0.007; a trend between the potency of statin treatment and the risk of RA was observed) [70] and lupus erythematosus (OR = 1.67) [71]. In the last study [71] cases were defined as drug-induced lupus reports.…”
Section: Rheumatic Diseases and Statin Intolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Les principaux médicaments inducteurs de lupus (procaïnamide, hydralazine, quinidine) n'ont, pour la plupart, plus d'autorisation de mise sur le marché en France. Des cas cliniques isolés, des séries de quelques cas (niveau de preuve 4) ainsi qu'une étude cas/non cas récente [36] suggèrent que des médicaments tels que certains inhibiteurs du système rénine-angiotensine et statines pourraient favoriser l'apparition du lupus ou d'une poussée de la maladie. Cependant, aucune donnée pertinente ne permet de contre-indiquer formellement la prescription de ces médicaments au cours du lupus.…”
Section: Objectifs Lipidiquesunclassified